Differential wing polyphenism adaptation across life stages under extreme high temperatures in corn leaf aphid - Chen, Yu (Sci Rep, 2019)
Polyphenism, a common phenomenon in nature, is an important form of adaptation in a diverse environment. Corn leaf aphid (CLA), Rhopalosiphum maidis, (Hemiptera: Aphididae), exhibit wing polyphenism in response to poor habitat quality. In this study, we focused on the effects of crowding and thermal cues on morph determination of CLA. Five developmental stages of aphids (1(st) to 4(th) nymphs and maternal adults) with increased population densities, were tested under two kinds of temperature patterns, i.e., A) a constant temperature of 22 °C with 2 h exposure to high temperature in the range of 35 to 39 °C during mid-photophase and B) different constant temperatures in the range of 22–30 °C with 2 h exposure to high temperature of 39 °C during mid-photophase. Crowding was found to directly impact winged induction. The 1(st) and 2(nd) nymphs were more sensitive for alate morphs induction under high density. In addition, temperature played a significant role in wing production, with the temperature setting of 26/39 °C in pattern B inducing higher alate morphs and survival than other temperature settings. Therefore, we hypothesize that warmer climate with brief high temperature is more favourable for survival and alate morphs production, but cool weather and transient extreme high temperature (>39 °C) is detrimental for CLA. Our results provide a new perspective on understanding the interactions between changes in extreme high temperatures and insect densities that differentially affect wing polymorphism for further demographic and distribution rates of species across temporal and spatial scales.